REMARKS ON THE KARSTIFICATION IN THE WIDER AREA OF THE UPPER MESSINIA CLOSED HYDROGEOLOGICAL BASIN (SW PELOPONNESUS, GREECE) - Mariolakos, I.; Spyridonos, E. (Bulletin of the Geological Society of Greece, 2010)
The Upper Messinia Basin is part of the Kalamata - Kyparissia graben structure, defined by two fault zones, one of E-W direction to the north and one of N-S direction to the east. The Tripolis and the Pindos alpidic units build up the basement of the region, and are covered by post-alpidic Pleistocene and quaternary deposits. The Basin is a closed hydrogeological system. In the upper cretaceous Pindos limestones, we observe two different karst types, according to drilling results. In the western part of the basin, where the limestones appear on the surface, the merokarst type is observed and water flow is limited in separated karstic conduits. On the contrary, in the central part of the basin, where the limestones underlie the clastic post-alpidic formations, the holokarst type is observed and a rich karstic aquifer is developed. This is explained by the closed hydraulic conditions. In the western part of the basin the karstic aquifer is unconfined, while in the central part it is confined, due to the overlying impermeable post-alpidic sediments and the overall closure of underground flow to the south. It appears that the confined conditions led to the development from merokarst to holokarst in this region.